Endothelial Progenitor Cell Dysfunction in Cardiovascular Diseases: Role of Reactive Oxygen Species and Inflammation. (30th December 2012) - Lin, Chih-Pei; Lin, Feng-Yen; Huang, Po-Hsun; Chen, Yuh-Lien; Chen, Wen-Chi; Chen, Huey-Yi; Huang, Yu-Chuen; Liao, Wen-Ling; Huang, Huey-Chun; Liu, Po-Len; Chen, Yung-Hsiang
Abstract : Endothelial progenitor cells (EPCs) move towards injured endothelium or inflamed tissues and incorporate into foci of neovascularisation, thereby improving blood flow and tissue repair. Patients with cardiovascular diseases have been shown to exhibit reduced EPC number and function. It has become increasingly apparent that these changes may be effected in response to enhanced oxidative stress, possibly as a result of systemic and localised inflammatory responses. The interplay between inflammation and oxidative stress affects the initiation, progression, and complications of cardiovascular diseases. Recent studies suggest that inflammation and oxidative stress modulate EPC bioactivity. Clinical medications with anti-inflammatory and antioxidant properties, such as statins, thiazolidinediones, angiotensin II receptor 1 blockers, and angiotensin-converting enzyme inhibitors, are currently administered to patients with cardiovascular diseases. These medications appear to exert beneficial effects on EPC biology. This review focuses on EPC biology and explores the links between oxidative stress, inflammation, and development of cardiovascular diseases.